A Low Cost Medical Image Digitization Setup For Enhancement And Analyzing of Conventional X-Ray Images - (:unkn) unknown (IEEE, 2013)
In medical industry, studies about storing, processing, analyzing and re-accessing the patient's information and images are intensively continuing. Both printed and digital medical images take more spaces than the others. In this paper, a mechanism which transfers easily the printed X-ray images to the digital environment enabling radiological assessment and archiving is set and a software is developed to help the analysis of those images. It is aimed to digitize the conventional images with a minimum loss while keeping the image quality. The setup which is in a closed box consists of a light source, a camera for image transfer and lenses. The software provides applying the image processing algorithms on digitized images and archiving them in DICOM format.
Keywords: image acquisition; image digitization; Matlab; IEEE 1394 camera; lens